2022
DOI: 10.3389/fphar.2022.1089066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical updates on tyrosine kinase inhibitors in HER2-positive breast cancer

Abstract: Breast cancer (BC) is caused by epigenetic modifications and genetic heterogeneity and exhibits various histological feature. HER2+ (Human epidermal growth factor receptor 2) is a more aggressive type of breast cancer, diagnosis and prognosis are difficult for HER2+ BC. Anti-HER2+ inhibitors have been effectively used for patient treatment. High mortality rate is reported in HER2+ BC, due to availability of limited therapeutic options. Despite advances in systemic medications to treat metastatic breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…The efficiency of EGFR‐TKIs used in targeted cancer treatment regimens is often restricted to the emergence of acquired resistance targeting drug‐resistant mutants of EGFR 10–12 . Currently, the available EGFR‐TKIs generally target the ATP binding site of the EGFR kinase domain, necessitating the need for therapeutic agents with alternative mechanisms of action for overcoming resistance to EGFR mutants 41 . Caporuscio et al have shown the design and development of small affinity molecules by a cost‐effective, high throughput docking method for identifying allosteric interaction sites of EGFR 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of EGFR‐TKIs used in targeted cancer treatment regimens is often restricted to the emergence of acquired resistance targeting drug‐resistant mutants of EGFR 10–12 . Currently, the available EGFR‐TKIs generally target the ATP binding site of the EGFR kinase domain, necessitating the need for therapeutic agents with alternative mechanisms of action for overcoming resistance to EGFR mutants 41 . Caporuscio et al have shown the design and development of small affinity molecules by a cost‐effective, high throughput docking method for identifying allosteric interaction sites of EGFR 42 .…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 , 12 Currently, the available EGFR‐TKIs generally target the ATP binding site of the EGFR kinase domain, necessitating the need for therapeutic agents with alternative mechanisms of action for overcoming resistance to EGFR mutants. 41 Caporuscio et al have shown the design and development of small affinity molecules by a cost‐effective, high throughput docking method for identifying allosteric interaction sites of EGFR. 42 To date, several clinical trials have been performed to assess the efficiency of TKIs in breast cancer and the results are ineffective owing to the monotherapy treatment regime.…”
Section: Discussionmentioning
confidence: 99%
“…Since trastuzumab is representative of the standard treatment of HER-2 positive breast tumors, we studied its effect in combination with the PPRHs against the ERBB2 gene. In this sense, the rationale for a combination of trastuzumab with either chemotherapy such as capecitabine or paclitaxel, or with tyrosine kinase inhibitors such as lapatinib, or more recently with a dual inhibitor of both mTOR and PI3K, has proved to be a more potent approach for HER-2-positive breast cancer treatment than trastuzumab alone [ 24 ]. Nowadays, the combined therapy of trastuzumab, pertuzumab, and taxane is the standard for treating metastatic breast cancer [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the reliability of HER2 as a target antigen, the types of HER2 inhibitors are diversifying. Currently, there are three main types of HER2 inhibitors used in clinical practice: small-molecule drugs (lapatinib, neratinib, tucatinib, and pyrotinib), monoclonal antibodies (trastuzumab, pertuzumab), and antibody-conjugated drugs (ADCs): TDM-1, T-DXd, et al ( Schlam and Swain, 2021 ; Singh et al, 2022 ; Banys-Paluchowski et al, 2023 ). For example, many guidelines recommend the combination of trastuzumab, pertuzumab, and taxane as the standard first-line treatment for patients with advanced HER2+ BC ( Swain et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%